2020
DOI: 10.1093/mmy/myaa036
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory evaluation of Mucorales PCR assays for testing serum specimens: A study by the fungal PCR Initiative and the Modimucor study group

Abstract: Interlaboratory evaluations of Mucorales qPCR assays were developed to assess the reproducibility and performance of methods currently used. The participants comprised 12 laboratories from French university hospitals (nine of them participating in the Modimucor study) and 11 laboratories participating in the Fungal PCR Initiative. For panel 1, three sera were each spiked with DNA from three different species (Rhizomucor pusillus, Lichtheimia corymbifera, Rhizopus oryzae). For panel 2, six sera with three conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Within the laboratories using the EPA assay, the only technical parameter, which demonstrated a significant impact on the result, was the qPCR platform, with Rotor-Gene achieving the lowest Cq values. Overall, the study demonstrated very good concordance in results throughout the laboratories and methods used [ 19 ].…”
Section: Dna-based Diagnosismentioning
confidence: 78%
See 2 more Smart Citations
“…Within the laboratories using the EPA assay, the only technical parameter, which demonstrated a significant impact on the result, was the qPCR platform, with Rotor-Gene achieving the lowest Cq values. Overall, the study demonstrated very good concordance in results throughout the laboratories and methods used [ 19 ].…”
Section: Dna-based Diagnosismentioning
confidence: 78%
“…Despite these difficulties, the Fungal PCR Initiative (FPCRI, www.fpcri.eu), working group of the ISHAM, aims to include PCR diagnostics in the EORTC/MSG criteria for fungal infections, which they achieved for Aspergillus PCR; Candida, Mucorales, and Pneumocystis PCR must follow. In this context, an inter-laboratory study on two simulated serum panels (spiked with Mucorales DNA) was performed in 2017-2018, with 23 European laboratories participating [19]. The study evaluated the reproducibility of different DNA extraction and qPCR methods.…”
Section: Potential and Limitations Of Molecular Diagnostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus PCR has demonstrated high sensitivity and high negative predictive value in severely immunocompromised patients in settings where antifungal prophylaxis is not used [78][79][80][81]. PCR is also an important diagnostic test for mucormycosis [82,83]. However, the performance of PCR from blood is impacted significantly in patients receiving mold-active antifungal agents as shown in a recent review [8,55,81,84].…”
Section: Nucleic Acid-based Assays/othersmentioning
confidence: 99%
“…The exact primer sequences are kept confidential by the manufacturer. Recently, the Fungal PCR Initiative (FPCRI) and the ModiMucor study group compared the performance of these assays using spiked serum in a ring test, and found the MucorGenius ® and Millon assays to have the highest positivity rates with the lowest Cq values [19].…”
Section: Introductionmentioning
confidence: 99%